Labelled Markov processes - Panangaden, P. (Prakash) (Imperial College Press ; Distributed by World Scientific Pub. Co., 2009)
Labelled Markov processes are probabilistic versions of labelled transition systems with continuous state spaces. The book covers basic probability and measure theory on continuous state spaces and then develops the theory of LMPs. The main topics covered are bisimulation, the logical characterization of bisimulation, metrics and approximation theory. An unusual feature of the book is the connection made with categorical and domain theoretic concepts.